2006
DOI: 10.1007/s11085-006-9021-2
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Oxidation of Ternary Alloys. VII: The Transition from the Internal to the External Oxidation of the Two Most-Reactive Components Under Intermediate Oxidant Pressures

Abstract: The conditions for the transition between the coupled internal oxidation of two most-reactive components and the formation of external scales in the scaling of ternary alloys under oxidant pressures below the stability of the oxide of the most-noble component, denoted as a situation of intermediate oxidant pressures, are examined under a number of simplifying conditions which allow to develop an approximate analytical treatment. If the precipitation of the two oxides occurs at the same front of internal oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…the reversed TEE by which the presence of Al is able to inhibit the internal oxidation of Zn, observed for all the ternary alloys containing 5 and 10 at.% Zn, may actually be explained by assuming again that the transition from the internal oxidation of B plus C beneath external AO scales to their external oxidation is controlled by the overall volume fraction of the internal oxides of these two alloy components, already used to explain Wagner's type of direct TEE [14][15][16][17]. From this point of view the elements B and C act cooperatively to establish the overall critical volume fraction of internal oxides, so that the addition of one of them reduces the critical content of the other component needed for the transition.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…the reversed TEE by which the presence of Al is able to inhibit the internal oxidation of Zn, observed for all the ternary alloys containing 5 and 10 at.% Zn, may actually be explained by assuming again that the transition from the internal oxidation of B plus C beneath external AO scales to their external oxidation is controlled by the overall volume fraction of the internal oxides of these two alloy components, already used to explain Wagner's type of direct TEE [14][15][16][17]. From this point of view the elements B and C act cooperatively to establish the overall critical volume fraction of internal oxides, so that the addition of one of them reduces the critical content of the other component needed for the transition.…”
Section: Discussionmentioning
confidence: 90%
“…The scaling behavior of the present system is first examined on the basis of a combination of the maps for the growth of external scales on ternary alloys calculated under high oxidant pressures, already examined in the past [13], with the critical conditions for the transitions between the various forms of internal and external oxidation [14][15][16][17]. The thermodynamic phase diagram and an approximate form of the oxidation map concerning the growth of external scales on Cu-Zn-Al alloys at 800°C is shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Gesmundo et al [29] has discussed the relationship between oxidation models of ternary A-B-C alloy (A<B<C, chemical activity) and the external oxygen pressure in pure oxidizing atmosphere, it is found that the lower the external oxygen pressure, the lower the critical contents of B and C needed to form their external scale. Combining the above two points, it can be deduced that the sputtered film decreases the partial pressure of oxygen at the coating/alloy interface from 10 -20 atm to a certain degree and promotes the selective oxidation of Si and Cr in the base alloy.…”
Section: Formation Mechanism Of the Protective Layermentioning
confidence: 99%
“…This paper presents a further analysis of the problem which, using the criterion of absence of supersaturation for the precipitation of the oxide of the component with intermediate reactivity at the most-external iof, provides a second basic equation allowing to calculate a single solution for the kinetics of displacement of both fronts in the case of double iof. The same analysis is extended to predict the critical conditions required to avoid this kind of internal oxidation, which have also been examined already separately for the conditions of low [3] and high [4] oxidant pressures.…”
Section: Introductionmentioning
confidence: 99%